THE STRATEGIC FUNCTION OF EDUCATION BETWEEN INHERITANCE AND SOCIO-CULTURAL CHANGE IN THE CIREBON ENVIRONMENT: A SOCIOLOGICAL APPROACH - Ratnaningsih, Fifit; Udin, Tamsik; Mulyana, Asep (PT. Altin Riset Publishing, 2025)
This article discusses the strategic function of education in the context of cultural and social heritage transmission and change in the Cirebon community, using a sociological approach. Education plays a role not only as a means of preserving local cultural values and traditions but also as an agent of change that encourages society to adapt to evolving social and cultural dynamics. This study examines how the education system in Cirebon strives to balance maintaining cultural heritage and responding to the challenges of modern social change. Using qualitative data and sociological analysis, the article reveals the crucial role of education in strengthening social and cultural identity while initiating constructive transformation within the Cirebon society.